Peran Lingkungan Keluarga Besar terhadap Perkembangan Anak Usia Dini - Putri, Sridevi Insani Cahaya (Lembaga Yasin AlSys, 2026)
The extended family plays an important role in early childhood development as a nonformal educational environment that unfolds naturally and continuously. Through interactions with grandparents, uncles, aunts, and cousins, children receive diverse socio-emotional, language, cognitive, and moral stimulation that supports early character formation and learning capacity. This article discusses the impact, role, and strategies of the extended family in supporting early childhood development, with an emphasis on the dynamics of everyday caregiving within the family environment. The findings indicate that the extended family provides caregiving support, role modeling, and contextual learning experiences, but may also generate problems when caregiving patterns among family members are not aligned. Therefore, strategies such as consistent communication regarding caregiving, the provision of educational play environments, sustained emotional support, collaboration with early childhood education (PAUD) institutions, and positive role modeling by all family members are required. In conclusion, the extended family is a crucial component in holistic child development and a strategic partner for formal educational institutions in optimizing the potential of young children.